Alternative and enhancing communication systems in critical units: A systematic review - Iparraguirre Vargas, Katherine Lluliana (2024)
Objective: To identify the scientific evidence on alternative and augmentative communication systems in critical units. Method: Bibliographic review of original articles carried out in the months of April-September 2023 in the databases of Medline (Pubmed), Cochrane Library, Scopus, Embase, Biblioteca en Salud (BVS), Web of Science, Science Direct, Scielo and Redalyc using the health sciences descriptors (Decs): Nursing; Nursing; Critical care nursing; Alternative and augmentative communication systems; Communication; Boolean operators AND and OR were used and different combinations were performed. Main results: 500 articles were identified and after employing the inclusion and exclusion criteria, 20 original studies were selected. Overall conclusion: Communication with patients is limited by clinical condition and biomedical devices. The systems used are Unaided (verbal, non-verbal and written communication) and Aided, low technology (pencil and paper, boards and pictograms) and high technology (speech valves and Tablet with mobile applications).